Sacral dural arteriovenous fistulas: a diagnostic and therapeutic challenge – single-centre experience of 13 cases and review of the literature. (12th October 2017) - Gioppo, Andrea; Faragò, Giuseppe; Giannitto, Caterina; Caputi, Luigi; Saladino, Andrea; Acerbi, Francesco; Ciceri, Elisa
Abstract : Background: Sacral dural arteriovenous fistulas (DAVFs) are rare vascular abnormalities of the spine characterised by slowly progressive symptoms that can mimic different myelopathy disorders. Object: To report our single Institution experience with sacral DAVFs. Methods: We retrospectively reviewed the clinical records of patients admitted from 1 January 2006 to 31 December 2016 with a diagnosis of sacral DAVFs, treated by endovascular embolisation or surgical clipping. Clinical presentation, imaging characteristics, treatment results and follow-up were analysed. Results: We identify 13 patients with sacral DAVFs supplied by lateral sacral arteries. Clinical presentation was characterised by different degrees of motor weakness and sphincter disturbances. In all patients, spinal MRI showed spinal cord hyperintensities with enhancement and prominent perimedullary vessels. Selective internal iliac angiography was mandatory to identify the exact location of the fistula. A complete embolisation was achieved in eight patients performing a single endovascular embolisation and in three patients performing a single surgical disconnection: two patients required combined procedures. Follow-up imaging showed a complete resolution of the spinal cord hyperintensities in 81% of patients and a reduction of the intramedullary enhancement in 91%. Gait improvement was observed in 73% of patients, while remaining stable in 27%. Sphincter disturbances improved in 36% of patients and remained stable in 64%. Conclusion: Awareness of sacral location of DAVFs is critical because standard spinal angiography will not identify sacral supplies, unless internal iliac arteries are properly examined. In our experience, the endovascular treatment show results comparable to surgery when the fistula point is correctly disconnected.